2015
DOI: 10.7748/ns.29.25.37.e9268
|View full text |Cite
|
Sign up to set email alerts
|

Washing uniforms at home: adherence to hospital policy

Abstract: Infection control is a priority for all hospitals to reduce the spread of healthcare-associated infections (HCAIs). Textiles especially uniforms, are a possible route of HCAI transmission. There are protocols to ensure hospital laundry services meet accepted standards, however healthcare uniforms are laundered by staff at home and variations in practice occur. A questionnaire was used to conduct a service evaluation at four hospitals in different NHS trusts to determine how closely healthcare staff followed ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…Energy saving and 'eco' settings were not selected. Biological detergent (most commonly used detergent used by nurses (Riley et al 2015)) was added as per instructions for a normal load of washing (17 ml dose per wash based on a 2-kg load).…”
Section: Launderingmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy saving and 'eco' settings were not selected. Biological detergent (most commonly used detergent used by nurses (Riley et al 2015)) was added as per instructions for a normal load of washing (17 ml dose per wash based on a 2-kg load).…”
Section: Launderingmentioning
confidence: 99%
“…A recent study reported that of 265 healthcare staff questioned, 44% launder uniforms below the recommended 60°C and 40% stated that they washed uniforms with everyday clothing. In addition, it is the responsibilities of individual trusts to interpret the DoH guidance on staff uniform washing, resulting in significant differences between the information given to nurses across the four trusts surveyed, with some trusts stating 60°C for 10 min while others just stating uniforms are to be washed at a minimum of 50°C, drying and the use of detergents are also often not clarified (Riley et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Polycotton treated with biological detergent and 0Á5% silver additive in the rinse phase was significantly antimicrobial (A values 1Á8-8Á9; Table 7), suggesting that cross contamination remaining after the wash could be inhibited by the antimicrobial textile finish. This study provides an insight into the most common low temperature washing parameters used by nurses (Riley et al 2015). There are a number of factors that may affect laundering performance, including the type of detergent, temperature and washing machine programme used; the parameters employed within this study may not represent those used by all healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…, Riley et al . ), which our institution also adopts, no question on washing temperature was asked in our questionnaire. Additional studies are required to determine the optimal temperature and laundry cycle for washing of veterinary HCW uniforms.…”
Section: Discussionmentioning
confidence: 99%